Belydenisvorming as kanonisering van geloofsoortuigings - Breytenbach, Andries (Hervormde teologiese studies, 2000)
The canonisation of religious convictions through the forming of creeds. This article deals with aspects of the process which underlies the shaping of formal creeds. Two stages are investigated: A preliminary stage in which a community of faith reacts in a polemic way to contextual questions or threats, and a secondary stage in which earlier confessions are canonised. Some of the implications of the canonisation of confessions of faith are scrutinised. The final conclusion is that the canonisation of one systematised understanding of faith runs afoul of the diversity of theologies and metaphoric language in the Old and New Testament.